СТРУКТУРНА ОПТИМІЗАЦІЯ БЕЗКОНТАКТНИХ МАГНІТОЕЛЕКТРИЧНИХ ТАХОГЕНЕРАТОРІВ - Кіреєв, В.Г.; Акинін, К.П.; Пєтухов, І.С.; Філоменко, А.А. (Інститут електродинаміки Національної академії наук України, 2025)
The paper is devoted to the structural optimization of brushless tachogenerators with permanent magnets on the rotor and a smooth slotless stator. The structures of rotors with surface-mounted magnets, with tangentially magnetized magnets, as well as with radially and tangentially magnetized magnets mounted on the magnetic core are considered. The effect of changing the rotor parameters on the form of the curve and the pulsation coefficient of the rectified EMF when installed in a stationary stator structure is analyzed. Recommendations are given for choosing the configuration of a brushless magnetoelectric tachogenerator with the lowest EMF pulsation.